The concept of al-'aql (the intellect) according to Al-Tabari, Al-Ghazali, and Muhammad Abduh : a comparative study - Al-Shafi'i, Mohammed Muneer' Deen Olodo (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This study examines the concept of the intellect according to three Imams (Muhammad al-Tabari, Muhammad al-Ghazali and Muhammad Abduh), with a view to ascertain how it is perceived theologically and philosophically, mostly through their respective Tafsir al-Tabari, Ihya Ulum al-Din (Kitab al-Ilm), and Tafsir al-Manar. The dissertation examines the conflicting views about the superiority of the intellect over the revelation or the revelation over the intellect, through comparatively ascertaining the Islamic conception of the right to intellect from the three ImÉms' perspectives. The dissertation ascertains that discussions around the concept of the intellect are not new, and that it will continue to be debated for a long time, most particularly its relationship and importance to the revelation and the Divine Commandments. From the study of the views of three scholars, the study reaffirms the theological, traditional, philosophical and intellectual positions of the intellect. Intellect, according to the three ImÉms, is an integral tool and means in comprehending the revelation for the benefits of knowing AllÉh (S.W.T.) and serving Him, and making life peaceful and worthy of living for fellow creatures. The study is based upon the primary and secondary sources and uses qualitative method for analysis and interpretation. The findings reveal that the intellect is Islamically as important as the revelation. The intellect can be seen in various ways and perceived differently, but essentially, it is the only distinctive property and characteristic of human being, which distinguishes him from all other creatures. The intellect is thus the base for al-TaklÊf and the karÉmah, the man is endowed with. Furthermore, the issue of using the intellect justly is the major reason why AllÉh (S.W.T.) has sent down the revelation and the Prophets and Messengers; AllÉh (S.W.T.) knows that man would not be able to reason properly if left alone without guidance, hence the necessity of sending the revelation to empower the intellect in its comprehension of both the written and cosmological signs of AllÉh (S.W.T.). The study uses twenty-seven cognates in the Qur'an to examine the Qur'anic-Islamic concept of the intellect; how it is viewed and used, and how its usages affect the community.